2002
DOI: 10.1007/s00330-002-1690-x
|View full text |Cite
|
Sign up to set email alerts
|

Covered stents in transjugular portosystemic shunt: healing response to non-porous ePTFE covered stent grafts with and without intraluminal irradiation

Abstract: The aim of this study was to evaluate the healing response to a new commercially available ePTFE-covered stent graft used to create transjugular intrahepatic portosystemic shunts (TIPS) in an animal model with and without intraluminal irradiation. The study was designed for ten domestic normotensive pigs. The TIPS was created using a ePTFE-covered stent graft (Viatorr, Gore, Flagstaff, Ariz.). Five animals were scheduled for intraluminal irradiation with iridium 192 immediately after TIPS creation with a dosag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2004
2004
2010
2010

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
(42 reference statements)
0
3
0
Order By: Relevance
“…The high rate of shunt insufficiency (40–60% at 1 year and 70–85% at 2 years after the TIPS procedure) made close surveillance and frequent costly revisions mandatory, thus rendering TIPS creation a multistage procedure in the majority of cases when bare stents were used 2,6 . Animal experiments 25–28 and preliminary clinical studies 29–34 suggested that the use of stents covered with PTFE could improve shunt patency by avoiding the pseudointimal and intimal hyperplasia. The expandable PTFE‐covered stent‐graft designed for TIPS comprises two portions: a 2‐cm‐long noncovered segment in the portal vein allows free blood flow to side branches of the portal vein through the bare nitinol stent wires; and the expandable PTFE portion covers the inside of the stent and is placed from the portal vein entry site along the length of the parenchymal tract as far as the hepatic vein ostium.…”
Section: Discussionmentioning
confidence: 99%
“…The high rate of shunt insufficiency (40–60% at 1 year and 70–85% at 2 years after the TIPS procedure) made close surveillance and frequent costly revisions mandatory, thus rendering TIPS creation a multistage procedure in the majority of cases when bare stents were used 2,6 . Animal experiments 25–28 and preliminary clinical studies 29–34 suggested that the use of stents covered with PTFE could improve shunt patency by avoiding the pseudointimal and intimal hyperplasia. The expandable PTFE‐covered stent‐graft designed for TIPS comprises two portions: a 2‐cm‐long noncovered segment in the portal vein allows free blood flow to side branches of the portal vein through the bare nitinol stent wires; and the expandable PTFE portion covers the inside of the stent and is placed from the portal vein entry site along the length of the parenchymal tract as far as the hepatic vein ostium.…”
Section: Discussionmentioning
confidence: 99%
“…Late shunt malfunction occurs in up to 80% of cases during follow-up. Recently, the use of expanded polytetrafl uoroethylene (ePTFE)-covered stents resulted in a primary patency rate of 84% at 1 year by Kaplan-Meier analysis [41][42][43][44][45] . Broad application is currently hampered by high costs.…”
Section: Technique and Procedural Complicationsmentioning
confidence: 99%
“…Gore and Associates, Flagstaff, AZ) has been tested on its safety and feasibility to be implanted in a TIPS both in an animal model and in humans [6,7,10]. The findings of the two published human pilot series demonstrate a high primary and secondary patency rate over 6 months to 1 year: Cejna et al described a 90% primary patency rate at 6 months, a 50% primary patency rate at 9 months and a secondary patency rate of 100% throughout the study in a mean follow-up of 289 days.…”
Section: Discussionmentioning
confidence: 99%